Kedudukan dan Tantangan Pembuktian Deepfake Evidence dalam Sistem Peradilan Pidana Indonesia - Ali Umar (Terang : Jurnal Kajian Ilmu Sosial, Politik dan Hukum, 2026)
The development of artificial intelligence has given rise to deepfake technology capable of realistically manipulating audio and visual content, thereby creating new challenges within Indonesia’s criminal evidentiary system. This study aims to analyze the legal position of deepfake evidence as electronic evidence and the challenges associated with its use in Indonesian criminal procedural law. The research employs a normative legal method using statutory and conceptual approaches. The findings indicate that electronic evidence has been recognized under the New Criminal Procedure Code and the Law on Electronic Information and Transactions; however, there are still no specific regulations governing the authentication of deepfake evidence. The ability of deepfake technology to produce highly convincing audiovisual manipulations makes the evidentiary process heavily dependent on scientific digital forensic examinations. In addition, limited facilities, inadequate human resources, and the absence of uniform authentication standards constitute major obstacles in law enforcement practices. Therefore, specific regulations, stronger digital forensic capabilities, and enhanced capacity of law enforcement officers are necessary to ensure legal certainty and the protection of human rights within criminal justice processes in the digital era.